Pacific urban development, water, and sanitation sector road map 2021 to 2025 (Asian Development Bank, 2021)
Urban development plays a key role in contributing to stronger, healthier, and more inclusive economies in the Pacific. This document provides an overview of the key constraints to sustainable urban development and more livable cities, as well as opportunities for deepening and scaling up ADB support and engagement in the region. The priority areas highlighted for ADB support are based on Pacific clients ongoing and emerging needs.